2021
DOI: 10.24036/10771171074
|View full text |Cite
|
Sign up to set email alerts
|

Design of Physical Teaching Materials Based on Cognitive Conflict Learning in Direct Current Electricity Integrating Virtual Laboratory

Abstract: Learning Physics in the 2013 Curriculum requires students to understand concepts. However, the facts found in the field show that students' understanding of concepts is still low and there are misconceptions, especially on unidirectional electricity. One solution to overcome this problem is to make physics teaching materials based on cognitive conflicts integrating virtual laboratories on unidirectional electrical materials to improve students' conceptual understanding. The aim pf this study was to produce a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“…So, it is concluded that the teaching materials on the feasibility of the content are valid. Accordance to the research of Lutfi, et.al [8] who obtained teaching materials with the category valid because the material presented is in accordance with the 2013 curriculum, the physics symbols used are correct, the material presented does not cause multiple interpretations, the teaching material contains cognitive conflict syntax.…”
Section: B Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…So, it is concluded that the teaching materials on the feasibility of the content are valid. Accordance to the research of Lutfi, et.al [8] who obtained teaching materials with the category valid because the material presented is in accordance with the 2013 curriculum, the physics symbols used are correct, the material presented does not cause multiple interpretations, the teaching material contains cognitive conflict syntax.…”
Section: B Discussionsupporting
confidence: 52%
“…Validation results are used as guidelines in revising the teaching materials and determining the feasibility of the teaching materials that have been made. The component of the feasibility of the content of the teaching material consists of (1) the description of the indicators in the teaching materials is in accordance with base competence 3.10 & 4.10, (2) The learning objectives of the teaching materials are in accordance with the indicators, (3) 4) The physics symbol used is correct, (5) The physics equation used is correct, (6) The physics term used is correct, (7) The image presented is in accordance with the material, (8) The phenomenon of physics is in accordance with the material, (9) The material presented does not cause multiple interpretations from students, (10) Images quoted from other people's work include references/sources, (11) Cognitive conflict-based teaching materials contain cognitive conflict syntax, namely activation of initial knowledge of misconceptions, presentation of cognitive conflict, discovery of concepts & equations and reflection, (12) Teaching materials made to integrate the real experiment video analysis correctly. So, it is concluded that the teaching materials on the feasibility of the content are valid.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, to find out the understanding of the material from the students after finishing learning, an evaluation was carried out. The evaluation results are still lacking because students do not understand the material that has been taught (Luthfi et al, 2021). Meanwhile, when the evaluation process at home the results are better because they are assisted by parents, while at school the results are different because of the results of their own abilities, so that the application of evaluation through online methods is less than optimal.…”
Section: B Submission Of Materialsmentioning
confidence: 99%
“…Curriculum development has been carried out from the Education Unit Level Curriculum (KUPTK) to the 2013 Curriculum which prioritizes student-centered learning and the teacher as a facilitator. Physics learning in the 2013 Curriculum has the aim that students can First Author(last name), et al Pillar of Physics Education, page.84-91 | 85 master concepts and have skills that are able to develop knowledge, move students to find their own problems that must be solved by educators using scientific approach methods [1].…”
Section: Introductionmentioning
confidence: 99%